2019
DOI: 10.4314/wsa.v45i2.08
|View full text |Cite
|
Sign up to set email alerts
|

Variable water quality of domestic wells emphasizes the need for groundwater quality monitoring and protection: Stinkwater, Hammanskraal, Gauteng

Abstract: Groundwater is a critical water resource in many peri-urban areas without municipal water supply, a common situation globally, but especially in Africa. These areas contain multiple water pollution risks from various human activities, including small industry, dumping, stock and pet animals, and pit latrines. Stinkwater village, 40 km north of Pretoria in Gauteng Province, that has only partial municipal water supply, was sampled for water quality from municipal taps, boreholes and open hand-dug wells. The wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Contrary to what other studies have found both internationally and nationally [11,22,32,33], the pathogenic microorganisms content present in drinking water in South Africa ranged within the acceptable and compliant limits stipulated in SANS 241:2015 Edition 2, leading to minimal health risks and health outcomes during the study period 2008 to 2018. Therefore, the high microbial water quality compliance statuses in South Africa were associated with the low occurrences of waterborne diseases and low child mortality and morbidity rates of children under five years in South Africa.…”
Section: Limitationcontrasting
confidence: 90%
See 1 more Smart Citation
“…Contrary to what other studies have found both internationally and nationally [11,22,32,33], the pathogenic microorganisms content present in drinking water in South Africa ranged within the acceptable and compliant limits stipulated in SANS 241:2015 Edition 2, leading to minimal health risks and health outcomes during the study period 2008 to 2018. Therefore, the high microbial water quality compliance statuses in South Africa were associated with the low occurrences of waterborne diseases and low child mortality and morbidity rates of children under five years in South Africa.…”
Section: Limitationcontrasting
confidence: 90%
“…These factors may include climate change, water stress, and the inadequate treatment of contaminated groundwater [19,20]. The provision of microbiologically contaminated water to populations serves as a threat to public health and is associated with the spread of infectious diseases, mortalities, and morbidities [10,11,21,22]. Based on recent trends, this study assesses diarrhoea among children under 5 years and microbial drinking water quality compliance in South Africa between the study period 2008-2018.…”
Section: Introductionmentioning
confidence: 99%
“…Some combination of these factors may be responsible, however, there is nothing to suggest this. NO3 2is commonly found associated with organic matter, most especially human and animal wastes (Baloyi & Diamond, 2019). As the area is used for stock farming (sheep mostly), the high NO3 2levels are not surprising, given the aridity will prevent dilution, and the aridity in combination with the low topographic gradients will prevent flushing of groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride is a critical nutrient for healthy bones and teeth, and when too low or high causes a variety of cosmetic to fatal health issues for bones and teeth (McGrady et al, 2012). Nitrate is an extremely widespread contaminant, especially in densely populated areas, or areas with poor sanitation (Baloyi & Diamond, 2019), but it is also known to occur in high levels naturally in southern Africa (Tredoux & Talma, 2006). It is generally accepted that it is a health risk, but the evidence for this is not that clear and may not be as dangerous as is commonly believed (Manassaram et al, 2006).…”
Section: Introductionmentioning
confidence: 99%